2015
DOI: 10.1111/jvec.12134
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus detection inAedes aegyptilarvae from southeastern Brazil

Abstract: The transmission of dengue, the most important arthropod-borne viral disease in Brazil, has been intensified over the past decades, along with the accompanying expansion and adaptation of its Aedes vectors. In the present study, we mapped dengue vectors in Ouro Preto and Ouro Branco, Minas Gerais, by installing ovitraps in 32 public schools. The traps were examined monthly between September, 2011 through July, 2012 and November, 2012 to April, 2013. The larvae were reared until the fourth stadium and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Transovarial transmission of dengue virus was documented in the field, where different serotypes of dengue virus in larvae or male adult mosquitoes were detected in different areas of the world. 14, 15, 16 A series of laboratory studies confirmed that Ae. aegypti and Ae.…”
Section: Introductionmentioning
confidence: 87%
“…Transovarial transmission of dengue virus was documented in the field, where different serotypes of dengue virus in larvae or male adult mosquitoes were detected in different areas of the world. 14, 15, 16 A series of laboratory studies confirmed that Ae. aegypti and Ae.…”
Section: Introductionmentioning
confidence: 87%
“…Six studies reported exclusively on dengue infection rates in wild mosquito populations (Table 2). Cecílio et al [175] observed four positive pools, out of 54 tested, among Aedes mosquitoes collected in two regions of Brazil over the course of 17 months, through the installation of ovitraps in public schools. Cruz et al [155] detected eight positive pools, out of 50 Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies examined natural infection rates of Zika virus [129,130], vertical transmission [179], or co-infection with other viruses [126]. This is in contrast to the wealth of research available on natural infection and co-infection for dengue and chikungunya viruses, although vertical transmission research was sparse for all three viruses [144,148,156,175,178,197,198]. Based on the internationally recognized urgency of Zika virus infection as a public health concern, and potential increase in the importance of this and other emerging arboviruses in the future, further research on arbovirus vectors and transmission dynamics is of pressing need.…”
Section: Discussionmentioning
confidence: 99%
“…Natural vertical transmission of DENV in Ae. aegypti has been demonstrated in the states of Minas Gerais 35,[37][38][39] , Pernambuco 40 , Ceará 36 , Mato Grosso [40][41][42] Rio de Janeiro 43 and Amazonas 44 .…”
Section: Discussionmentioning
confidence: 99%